Comparative study of albumen pH and whole egg pH for the evaluation of egg freshness. Issue 9 (21st October 2017) - Dong, Xiaoguang; Dong, Jun; Peng, Yankun; Tang, Xiuying
ABSTRACT: The Haugh unit (HU) is the most widely used measure to assess egg freshness. It is crucial and difficult to measure albumen height as a variable of the HU, especially for stale eggs. Albumen pH is strongly correlated to the HU and rarely affected by age or strain, except for storage. The prediction of albumen pH is a better indicator of egg freshness than the HU. Albumen is separated from the yolk in the albumen pH test, while in the whole egg pH measurement, it is not necessary to separate the albumen from the yolk. The objective of this research was to compare the albumen pH with the whole egg pH using visible near-infrared spectroscopy. Spectra were acquired using transmitted light on white-shelled eggs. Pretreatment methods containing multiplicative scatter correction, the standard normal variate (SNV), the first derivative, and the second derivative were used. A partial least square regression (PLSR) was used to set up prediction models. The results illustrated that PLSR models preprocessed by the SNV of albumen pH and whole egg pH were superior to other models. In the best prediction models, the correlation coefficients for albumen pH and whole egg pH were 0.923 and 0.752, and the root mean square error values were 0.170 and 0.265, respectively. The prediction models of albumen pH were better than those of whole egg pH using the PLSR method. In addition, the relevant information concerning albumen pH and whole egg pH ranged from 550 to 850 nm.